2020
DOI: 10.1017/s0033291719004124
|View full text |Cite
|
Sign up to set email alerts
|

Emotional recognition training modifies neural response to emotional faces but does not improve mood in healthy volunteers with high levels of depressive symptoms

Abstract: Background There is demand for new, effective and scalable treatments for depression, and development of new forms of cognitive bias modification (CBM) of negative emotional processing biases has been suggested as possible interventions to meet this need. Methods We report two double blind RCTs, in which volunteers with high levels of depressive symptoms (Beck Depression Inventory ii (BDI-ii) > 14) completed a brief course of emotion recognition training (a novel form of CBM using fac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 40 publications
2
16
0
Order By: Relevance
“…Here we report two studies that investigated the effectiveness of EBT when remotely delivered as a digital therapeutic, in both healthy participants and individuals currently taking SSRIs for anxiety or depression. In both, EBT was successful in producing lasting positive changes in facial emotion perception, with effects comparable to those found in laboratory-based studies (Penton-Voak et al, 2012, 2020. These changes have previously been shown to transfer to novel faces (Dalili et al, 2017), suggesting that a short course of EBT has the potential to influence participants' wider social encounters.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Here we report two studies that investigated the effectiveness of EBT when remotely delivered as a digital therapeutic, in both healthy participants and individuals currently taking SSRIs for anxiety or depression. In both, EBT was successful in producing lasting positive changes in facial emotion perception, with effects comparable to those found in laboratory-based studies (Penton-Voak et al, 2012, 2020. These changes have previously been shown to transfer to novel faces (Dalili et al, 2017), suggesting that a short course of EBT has the potential to influence participants' wider social encounters.…”
Section: Discussionsupporting
confidence: 65%
“…A recent neuroimaging study found that EBT alters emotional processing by increasing neural activation in response to happy facial expression (Penton-Voak et al, 2020). After five sessions, participants showed increased activity in the medial prefrontal cortex and bilateral amygdala when viewing a novel set of happy faces.…”
Section: Emotional Bias Training As a Treatment For Anxiety And Deprementioning
confidence: 98%
“…Indeed, packages of emotion recognition training are being developed to address this issue (e.g. the study by Penton-Voak et al 78 ).…”
Section: Limitations and Recommendations For Future Researchmentioning
confidence: 99%
“…However, the direction of effect is unclear; social autistic traits may contribute to deficits in emotion recognition, or these deficits may contribute to, or exacerbate social autistic traits. Since emotion recognition is a potentially modifiable target (Penton‐Voak et al., 2020 ; Penton‐Voak, Bate, Lewis, & Munafò, 2012 ; Rawdon et al., 2018 ), a better understanding of its relationship with ASD and social autistic traits, including the direction of association, may help inform management and treatment of ASD.…”
Section: Introductionmentioning
confidence: 99%